2001
DOI: 10.4141/s00-074
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 solid-state NMR of soil organic matter - using the technique effectively

Abstract: ).Preston, C. M. 2001. Carbon-13 solid-state NMR of soil organic matter -using the technique effectively. Can. J. Soil Sci. 81: 255-270. Solid-state 13 C CPMAS NMR offers many options for characterizing carbon in soil organic matter (SOM). Its effectiveness, however, is often limited by a poor understanding of the techniques, and lack of hands-on access and training opportunities for students. Of nearly 250 modern NMR systems in Canada, approximately one is genuinely available for SOM studies, and there is poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 110 publications
5
105
0
Order By: Relevance
“…The total integrated area of CP spectra was 0.42-0.49 of that observed for the corresponding BD spectra (i.e., CP enhancement was < 0.5 compared to a theoretical maximum of 4). The discrepancy is even larger, as CP efficiency is reduced at high spinning speeds (Jakobsen et al, 1988), and the compensating ramped-amplitude technique (RAMP) was not available on our equipment (Preston, 2001). For three other chars derived from wood in wildfires, we found that CP efficiency at 8000 Hz was 0.57-0.73 of that at 4700 Hz (unpublished results).…”
Section: Cp Efficiency For Charsmentioning
confidence: 87%
See 3 more Smart Citations
“…The total integrated area of CP spectra was 0.42-0.49 of that observed for the corresponding BD spectra (i.e., CP enhancement was < 0.5 compared to a theoretical maximum of 4). The discrepancy is even larger, as CP efficiency is reduced at high spinning speeds (Jakobsen et al, 1988), and the compensating ramped-amplitude technique (RAMP) was not available on our equipment (Preston, 2001). For three other chars derived from wood in wildfires, we found that CP efficiency at 8000 Hz was 0.57-0.73 of that at 4700 Hz (unpublished results).…”
Section: Cp Efficiency For Charsmentioning
confidence: 87%
“…Therefore, CPMAS spectra typically underrepresent amorphous long-chain CH 2 and the polycondensed structures of BC (Maroto-Valer et al, 1996;Skjemstad et al, 1999;Smernik and Oades, 2000;Freitas et al, 2001;Preston, 2001;Preston et al, 2002;Baldock and Smernik, 2002). To overcome this, we also obtained spectra using simple Bloch decay (BD) acquisition (without CP), with 720 scans and 100 s recycle time as determined to be sufficient for char samples by Smernik and Oades (2000) and Baldock and Smernik (2002).…”
Section: Solid State 13 C Nmr Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…The question invariably associated with soil organic matter (SOM) studies is whether to work with intact soil or to fractionate and if so, how. The early emphasis on humic and fulvic acids (HA, FA) and the often acrimonious debate on their relevance, was driven in part by the need to isolate those SOM forms which are both high in carbon and reasonably soluble and thus, most amenable to the chemical and spectroscopic techniques then available [7]. Instead, recently developed modern analytical techniques like Solid-state NMR offers great potential as a technique for identifying and quantifying the different forms of organic C in soil [8][9].…”
mentioning
confidence: 99%